1999
DOI: 10.1111/j.1574-6968.1999.tb13738.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the mycobacterial cell entry gene ofMycobacterium bovisBCG results in a mutant that exhibits a reduced invasiveness for epithelial cells

Abstract: Mycobacteria belonging to the Mycobacterium tuberculosis complex have the ability to invade and replicate in non-phagocytic cells, an event that requires the presence of bacterial surface components capable of triggering a cell response and the subsequent internalization of the microorganism. In this study, we report the sequencing of the mycobacterial cell entry gene (mce) of Mycobacterium bovis bacillus Calmette-Guérin (BCG) and the generation and characterization of a mutant BCG strain with an inactivated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Interestingly, in contrast to pathogenic M. avium TMC724, conditionally pathogenic M. avium 104 contains 2 additional clusters of mce genes, MAV_2532-2537 and MAV_5047-5051 located in LSPs 14 and 22, respectively. The mce operons have been implicated in the pathogenesis of mycobacteria, and their products were suggested to be transporter systems [29], [30], [31], [32].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in contrast to pathogenic M. avium TMC724, conditionally pathogenic M. avium 104 contains 2 additional clusters of mce genes, MAV_2532-2537 and MAV_5047-5051 located in LSPs 14 and 22, respectively. The mce operons have been implicated in the pathogenesis of mycobacteria, and their products were suggested to be transporter systems [29], [30], [31], [32].…”
Section: Resultsmentioning
confidence: 99%
“…We screened this list initially for the presence of genes previously shown to be required for survival of mycobacteria in macrophages. Insertions with a high fitness cost include those in a known virulence locus involved in synthesis and transport of phthiocerol dimycocerosate (DIM), a complex lipid component of the mycobacterial cell wall [32,33], and in the mycobacterial cell entry 1 (mce1) region (Rv0169–Rv0178), which has been implicated in mycobacterial entry to host cells [3537] and is required for virulence in a mouse model (Figure 2) [30]. Reduced fitness (FR < 0.5; false discovery rate [FDR] = 1%) was also associated with a series of insertions in the pathway for conversion of isocitrate to glucose (Table S3)—isocitrate lyase ( icl, Rv0467), PEP carboxykinase ( pcka, Rv0211) and fructose-1,6-bisphosphatase (Rv1099c)—consistent with previous proposals that mycobacteria rely predominantly on lipid substrates for intracellular metabolism [38].…”
Section: Resultsmentioning
confidence: 99%
“…A considerable number of studies have demonstrated that Mce proteins are related to the virulence of each member of the M. tuberculosis complex. Flesselles et al [5] have reported that a BCG strain mutated in mce1 exhibits a reduced ability to invade the non-phagocytic epithelial cell line HeLa. Sassetti and Rubin [6] have then found that mce1 disruption causes attenuation of M. tuberculosis .…”
Section: Introductionmentioning
confidence: 99%